A game-based algorithm for fair bandwidth allocation in Fibre-Wireless access networks - Coimbra, J.; Schütz, G.; Correia, N. (Optical switching and networking, 2013)
Fibre-Wireless (FiWi) access networks have been proposed as flexible and cost-effective solutions for future access networks. At the wireless mesh section, wireless routers have to forward both local traffic from directly connected users and foreign traffic from neighbour wireless routers. How to allocate resources to local and foreign traffic at each router in a balanced way, while avoiding starvation of routers requiring less resources, is a fundamental issue that must be solved so that new services emerge. Here, we develop a repeated game framework for bandwidth allocation and propose an algorithm that allocates bandwidth in a fair manner. The algorithm is able to detect over claiming routers and avoid possible denial of service that these may cause to others. Moreover, unfruitful use of resource is prevented, avoiding the forwarding of packets that would be dropped at some point later in the path, and queueing delay conditions are kept similar among local and foreign traffic. These fair network conditions open way for QoS support since it is easier to ensure the operationality of services.